Peran Identitas Nasional Dalam Membangun Karakter Bangsa: Studi Kasus Pembentukan Nilai-Nilai Pancasila di Indonesia - Sulistya, Widya Puspita; Sairah, Rani; Zulkarnain, Adam Putra (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to identify and analyze the role of national identity, especially Pancasila values, in shaping the character of the Indonesian nation, as well as exploring how these values can be applied effectively in people's daily lives. The research method used is a qualitative approach with a library research type of research, where secondary data is obtained from various sources such as books, scientific journals and official websites that are relevant to the research topic. The data analysis technique follows the Miles and Huberman method, which includes data reduction, data presentation, and drawing conclusions. The research results highlight that Pancasila values, such as justice, unity and democracy, play a crucial role in forming a strong national character and integrity. Through education and the application of Pancasila values in everyday life, the younger generation is taught to understand, respect and apply these principles in social and community interactions. Thus, Pancasila not only strengthens national identity, but also forms a national character with noble personalities, maintaining harmony, equality and justice in society. Continuous efforts to maintain and strengthen national identity and Pancasila values are crucial steps in building a strong and high-quality national character.